When Policy Meets Practice: The Dilemma for Guidance on Risk Assessment Under the Cartagena Protocol on Biosafety - Hokanson, Karen E. (Frontiers in Bioengineering and Biotechnology, 2019)
The Conference of the Parties serving as the meeting of the Parties (COP-MOP) to the Cartagena Protocol on Biosafety to the Convention on Biological Diversity decided years ago to undertake the development of guidance on risk assessment of living modified organisms (LMOs) resulting from modern biotechnology, in order to assist the Parties to the protocol to conduct risk assessments in line with the principles and methodology described therein. After many years of working through ad hoc technical expert groups (AHTEG) and open-ended online forum discussions, including an extensive process to test and revise the guidance document, the COP-MOP did not decide to endorse the last version of the document when it was finally presented to them. A failure to achieve consensus that the guidance, as it had evolved, is relevant and useful is seen as a potential setback for many Parties to the protocol with little to no experience with risk assessment. There are a number of reasons for the lack of success in this attempt to develop useful guidance on risk assessment, including a poorly defined and shifting purpose, misplaced expertise, and a misguided testing process, mostly perpetuated by the constraints of using processes of the Convention. These problems with the development of the Guidance on Risk Assessment of LMOs are explored here in an effort to elucidate the missteps that should be avoided and the lessons that can be learned. Most prominent is a need to rely upon the expanding past and present experiences with actual cases of risk assessments of LMOs, if there is to be any further attempt to develop guidance on risk assessment under the Convention and its protocol.